2020
DOI: 10.1016/j.carbpol.2020.116428
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of mucoadhesive electrospun chitosan/polyethylene oxide nanofibers facilitates adhesion to the sublingual mucosa

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Mucoadhesive CS-based electrospun nanofibers have been reported to be promising candidates for overcoming challenges associated with sublingual drug delivery. For example, Stie et al [198] focused on the elucidation of the mucoadhesive properties of chitosan/polyethylene oxide (PEO) nanofibers. They studied how the degree of deacetylation (DDA, 53-96%) of CS influenced their morphological and mucoadhesive properties.…”
Section: Buccal Drug Deliverymentioning
confidence: 99%
“…Mucoadhesive CS-based electrospun nanofibers have been reported to be promising candidates for overcoming challenges associated with sublingual drug delivery. For example, Stie et al [198] focused on the elucidation of the mucoadhesive properties of chitosan/polyethylene oxide (PEO) nanofibers. They studied how the degree of deacetylation (DDA, 53-96%) of CS influenced their morphological and mucoadhesive properties.…”
Section: Buccal Drug Deliverymentioning
confidence: 99%
“…For example, the solvent of chitosan is generally toxic or an irritating liquid such as acetic acid, trifluoroacetic acid, HFIP, CF, etc. ; there are fiber beads in the process of electrospinning chitosan; the mechanical properties of the nanofibers are weak [ 114 , 115 , 116 ]. To avoid the use of toxic or irritating solvents such as HFIP, CF, TFA, and acetic acid, chitosan can be modified and made water-soluble.…”
Section: Antibacterial Materialsmentioning
confidence: 99%
“…However, the highest swelling ratio was achieved under acidic pH (4.01) conditions for the CS/PEO but the water sorption in solutions after 24 h showed that the swelling ratio of the composite nanofiber membranes decreased. This observed weight loss could be because CS with very high DDA may be dispersible in a slightly acidic medium (pH < 6) or due to some small quantity of the CS/PEO becoming soluble [59].…”
Section: Swelling Behavior Of the Composite Nanofiber Membranementioning
confidence: 99%